Time-Averaged Wavefront Analysis Demonstrates Preferential Pathways of Atrial Fibrillation, Predicting Pulmonary Vein Isolation Acute Response - Roney, Caroline H.; Child, Nicholas; Porter, Bradley; Sim, Iain; Whitaker, John; Clayton, Richard H.; Laughner, Jacob I.; Shuros, Allan; Neuzil, Petr; Williams, Steven E.; Razavi, Reza S.; O'Neill, Mark; et al. (Frontiers in Physiology, 2021)
Electrical activation during AF appears chaotic and disorganized, which impedes characterization of the underlying substrate and treatment planning. While globally chaotic, there may be local preferential activation pathways that represent potential ablation targets. The aim of this study was to identify preferential activation pathways during Atrial Fibrillation (AF) and predict the acute ablation response when these are targeted by pulmonary vein isolation (PVI). In persistent AF patients (n=14), simultaneous biatrial contact mapping with basket catheters was performed pre-ablation and following each ablation strategy (PVI, roof and mitral lines). Unipolar wavefront activation directions were averaged over 10 s to identify preferential activation pathways. Clinical cases were classified as responders or non-responders to PVI during the procedure. Clinical data were augmented with a virtual cohort of 100 models. In AF pre-ablation, pathways originated from the pulmonary vein (PV) antra in PVI responders (7/7), but not in PVI non-responders (6/6). We propose a novel index that measures activation waves from the PV antra into the atrial body. This index was significantly higher in PVI responders than non-responders (clinical: 16.3% vs 3.7%, p=0.04; simulated: 21.1% vs 14.1%, p=0.02). Overall, this novel technique and proof of concept study demonstrates that preferential activation pathways exist during AF. Targeting patient-specific activation pathways that flowed from the PV antra to the left atrial body using PVI terminated AF during the procedure. These PV activation flow pathways may correspond to the presence of drivers in the PV regions.